Cocatalyzing Pt/PtO Phase-Junction Nanodots on Hierarchically Porous TiO2 for Highly Enhanced Photocatalytic Hydrogen Production - Ren, Xiao-Ning; Hu, Zhi-Yi; Jin, Jun; Wu, Liang; Wang, Chao; Liu, Jing; Liu, Fu; Wu, Min; Li, Yu; Tendeloo, Gustaaf Van; Su, Bao-Lian (ACS applied materials & interfaces, 2017)
Phase-junctions between a cocatalyst and its semiconductor host are quite effective to enhance the photocatalytic activity and are widely studied, while reports on the phase-juncted cocatalyst are still rare. In this work, we report the deposition of the Pt/PtO phase-juncted nanodots as cocatalyst via NaOH modification of an interconnected meso-macroporous TiO2 network with high surface area and inner-particle mesopores to enhance the performance of photocatalytic H2 production. Our results show that NaOH modification can largely influence Pt/PtO phase-juncted nanodot formation and dispersity. Compared to the TiO2 nanoparticles, the hierarchically meso-macroporous TiO2 network containing 0.18 wt % Pt/PtO phase-juncted cocatalyst demonstrates a highest photocatalytic H2 rate of 13 mmol g-1 h-1 under simulated solar light, and possesses a stable cycling activity without obvious decrease after five cycles. Such high H2 production performance can be attributed to both the phase-juncted Pt/PtO providing more active sites while PtO suppresses the undesirable hydrogen back reaction, and the special hierarchically porous TiO2 network with inner-particle mesopores presenting short diffusion path lengths for photogenerated electrons and enhanced light harvesting efficiency. This work suggests that Pt/PtO phase-juncted cocatalyst on hierarchically porous TiO2 nanostructures is a promising strategy for advanced photocatalytic H2 production.Phase-junctions between a cocatalyst and its semiconductor host are quite effective to enhance the photocatalytic activity and are widely studied, while reports on the phase-juncted cocatalyst are still rare. In this work, we report the deposition of the Pt/PtO phase-juncted nanodots as cocatalyst via NaOH modification of an interconnected meso-macroporous TiO2 network with high surface area and inner-particle mesopores to enhance the performance of photocatalytic H2 production. Our results show that NaOH modification can largely influence Pt/PtO phase-juncted nanodot formation and dispersity. Compared to the TiO2 nanoparticles, the hierarchically meso-macroporous TiO2 network containing 0.18 wt % Pt/PtO phase-juncted cocatalyst demonstrates a highest photocatalytic H2 rate of 13 mmol g-1 h-1 under simulated solar light, and possesses a stable cycling activity without obvious decrease after five cycles. Such high H2 production performance can be attributed to both the phase-juncted Pt/PtO providing more active sites while PtO suppresses the undesirable hydrogen back reaction, and the special hierarchically porous TiO2 network with inner-particle mesopores presenting short diffusion path lengths for photogenerated electrons and enhanced light harvesting efficiency. This work suggests that Pt/PtO phase-juncted cocatalyst on hierarchically porous TiO2 nanostructures is a promising strategy for advanced photocatalytic H2 production.